rut gon bieu thuc sau
A=5x-2-/2x+1/
cho A= (2x-1)^2 -5x.(x-1)+2.(x+1).(x-2) rut gon bieu thuc A
\(A=\left(2x-1\right)^2-5x\left(x-1\right)+2\left(x+1\right)\left(x-2\right)\)
\(=4x^2-4x+1-5x^2+5x+2\left(x^2-x-2\right)\)
\(=x^2-x-3\)
rut gon bieu thuc a,(3x+2)^2+4x-3^2+2(5x-2)(5x+2)-75x^2
b,(x-2)^3+(2x+1)^3++2(x+2)(1-x)-9x^3+2x
a: \(\left(3x+2\right)^2+4x-3x^2+2\left(5x-2\right)\left(5x+2\right)-75x^2\)
\(=9x^2+12x+4+4x-3x^2+50x^2-8-75x^2\)
\(=-19x^2+16x-4\)
rut gon bieu thuc :P=5x(x-3)(x+3)-(2x-3)^2+34x(x+2)-5(x+2)^3+25x-1
\(:P=5x(x-3)(x+3)-(2x-3)^2+34x(x+2)-5(x+2)^3+25x-1\)
\(P=5x(x^2-9)-(4x^2-12x+9)+34x^2+68x-5(x^3+6x^2+12x+8)+25-1\)
\(P=5x^3-45x-4x^2+12x-9+34x^2+68x-5x^3-30x^2-60x-40+25-1\)
\(P=(5x^3-5x^3)+(34x^2-4x^2-30x^2)+(12x-45x++68x+25x-60x)-(9+1)\)
\(P=-10\)
rut gon bieu thuc
(2x-1).(x-2)
rut gon bieu thuc 2ax^2-a(1+2x^2)-[a-x(x+a)]
2ax^2-a(1+2x^2)-[a-x(x+a)]
=2ax2-2ax2+a+x2-ax+a
=(2ax2-2ax2)-(a+a)+ax+x2
=0-2a+ax+x2
=x2+ax-2a
Rut gon bieu thuc sau: 2x*(2x-1)2-3x*(x+3)2-4x*(x+1)2
rut gon bieu thuc: 2x2(x-2) - 2x(x-1)(x+1)
\(2x^2\left(x-2\right)-2x\left(x-1\right)\left(x+1\right)=2x^3-4x^2-2x^3+2x=-4x^2+2x=-2x\left(2x-1\right)\)
\(2x^2\left(x-2\right)-2x\left(x-1\right)\left(x+1\right)\)
\(=2x^3-4x^2-2x\left(x^2-1\right)\)
\(=2x^3-4x^2-2x^3+2x=-4x^2+2x\)
1 rut gon bieu thuc ; A=5Ix+1I-3.[4-2x]
Rut gon bieu thuc
a) x(2x2-3)-x2(5x+1)+x2
b)3x(x-2)-5x(1-x)-8(x2-3)